Get expert advice and community support on IDNLearn.com. Discover in-depth answers to your questions from our community of experienced professionals.
Sagot :
Sure, let's start by combining the like terms in the polynomial [tex]\(x y - 2 x y + 3 x^2 y - 4 x y^2 + 2 x y^2 - x y - 2 x y^2 + 3 x^2 y\)[/tex].
1. Identify and Combine Like Terms:
- Terms involving [tex]\(xy\)[/tex]: [tex]\(x y - 2 x y - x y\)[/tex]
- Terms involving [tex]\(x^2 y\)[/tex]: [tex]\(3 x^2 y + 3 x^2 y\)[/tex]
- Terms involving [tex]\(x y^2\)[/tex]: [tex]\(-4 x y^2 + 2 x y^2 - 2 x y^2\)[/tex]
Combining these like terms, we get:
- [tex]\(x y - 2 x y - x y = (1 - 2 - 1)xy = -2xy\)[/tex]
- [tex]\(3 x^2 y + 3 x^2 y = (3 + 3)x^2 y = 6x^2 y\)[/tex]
- [tex]\(-4 x y^2 + 2 x y^2 - 2 x y^2 = (-4 + 2 - 2)x y^2 = -4x y^2\)[/tex]
So the polynomial simplifies to:
[tex]\[ -2xy + 6x^2y - 4xy^2 \][/tex]
2. Evaluate the Polynomial for [tex]\(x = 4\)[/tex] and [tex]\(y = -2\)[/tex]:
[tex]\[ -2xy + 6x^2y - 4xy^2 \][/tex]
Substituting [tex]\(x = 4\)[/tex] and [tex]\(y = -2\)[/tex]:
[tex]\[ -2(4)(-2) + 6(4^2)(-2) - 4(4)(-2)^2 \][/tex]
3. Calculate Each Term:
- For [tex]\(-2xy\)[/tex]:
[tex]\[ -2(4)(-2) = 16 \][/tex]
- For [tex]\(6x^2y\)[/tex]:
[tex]\[ 6(4^2)(-2) = 6(16)(-2) = 6 \times -32 = -192 \][/tex]
- For [tex]\(-4xy^2\)[/tex]:
[tex]\[ -4(4)(-2)^2 = -4(4)(4) = -4 \times 16 = -64 \][/tex]
4. Combine the Results:
[tex]\[ 16 - 192 - 64 = 16 - 256 = -240 \][/tex]
Thus, the final evaluated value of the combined polynomial for [tex]\(x = 4\)[/tex] and [tex]\(y = -2\)[/tex] is:
[tex]\[ -240 \][/tex]
1. Identify and Combine Like Terms:
- Terms involving [tex]\(xy\)[/tex]: [tex]\(x y - 2 x y - x y\)[/tex]
- Terms involving [tex]\(x^2 y\)[/tex]: [tex]\(3 x^2 y + 3 x^2 y\)[/tex]
- Terms involving [tex]\(x y^2\)[/tex]: [tex]\(-4 x y^2 + 2 x y^2 - 2 x y^2\)[/tex]
Combining these like terms, we get:
- [tex]\(x y - 2 x y - x y = (1 - 2 - 1)xy = -2xy\)[/tex]
- [tex]\(3 x^2 y + 3 x^2 y = (3 + 3)x^2 y = 6x^2 y\)[/tex]
- [tex]\(-4 x y^2 + 2 x y^2 - 2 x y^2 = (-4 + 2 - 2)x y^2 = -4x y^2\)[/tex]
So the polynomial simplifies to:
[tex]\[ -2xy + 6x^2y - 4xy^2 \][/tex]
2. Evaluate the Polynomial for [tex]\(x = 4\)[/tex] and [tex]\(y = -2\)[/tex]:
[tex]\[ -2xy + 6x^2y - 4xy^2 \][/tex]
Substituting [tex]\(x = 4\)[/tex] and [tex]\(y = -2\)[/tex]:
[tex]\[ -2(4)(-2) + 6(4^2)(-2) - 4(4)(-2)^2 \][/tex]
3. Calculate Each Term:
- For [tex]\(-2xy\)[/tex]:
[tex]\[ -2(4)(-2) = 16 \][/tex]
- For [tex]\(6x^2y\)[/tex]:
[tex]\[ 6(4^2)(-2) = 6(16)(-2) = 6 \times -32 = -192 \][/tex]
- For [tex]\(-4xy^2\)[/tex]:
[tex]\[ -4(4)(-2)^2 = -4(4)(4) = -4 \times 16 = -64 \][/tex]
4. Combine the Results:
[tex]\[ 16 - 192 - 64 = 16 - 256 = -240 \][/tex]
Thus, the final evaluated value of the combined polynomial for [tex]\(x = 4\)[/tex] and [tex]\(y = -2\)[/tex] is:
[tex]\[ -240 \][/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com has the solutions to your questions. Thanks for stopping by, and come back for more insightful information.